Penggunaan Musala sebagai Tempat Iktikaf Wanita (Studi pada Asrama Putri STIBA Makassar) - Siti Sa'dianti; Akrama Hatta; Aswin Aswin (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2022)
This research aims to find out and understand the use of the STIBA Makassar women's dormitory prayer room as a place for women's iktikaf. The problems raised in the research are; First, what is the phenomenon of using the STIBA Makassar women's dormitory prayer room as a place of itikaf; and Second, what is the law regarding the use of the STIBA Makassar women's dormitory prayer room as a place of iktikaf for women. This type of research is descriptive qualitative with data collection methods through field research using a normative approach, phenomenological approach and conceptual approach. The research results are as follows; First, the phenomenon of using the STIBA Makassar women's dormitory prayer room as a place for women's iktikaf in terms of facilities is very feasible, but according to Sharia it still needs discussion; and Second, the law uses the STIBA Makassar women's dormitory prayer room as a place of iktikaf, namely: Jumhur ulama rejects its validity, Ḥanafiyyah says it is afdal, and STIBA Makassar does not allow it.